TeraCale: Integrated laser irradiation and chemical etching with IoT automatization as a solution for sustainable crystalline-sillicone photovoltaic panel waste recycling system - Emmanuela Graceika Chelsea Kristiana; Najwa Laili Fajri; Tasya Syifa Alfadhiilah (Waste Handling and Environmental Monitoring, 2026)
Background: The rapid expansion of global renewable energy capacity resulted in a significant increase in crystalline-silicon (c-Si) photovoltaic (PV) panel installations, which are projected to generate up to 78 million tonnes of end-of-life (EoL) waste by 2050. Existing recycling methods, including pyrolysis, mechanical shredding, and organic solvent dissolution, are often associated with high energy demands, toxic emissions, and the risk of damaging valuable solar cells. This study aims to present TeraCale, an innovative recycling system that integrates laser irradiation and chemical etching with Internet of Things (IoT) automation to deliver a sustainable and economically viable solution for c-Si panel waste. Methods: This study is formulating the idea of innovation by collecting and analyzing the data from various journals. The methodology comprises a three-stage treatment process, such as initial hydraulic dismantling of frames using Programmable Logic Controllers (PLC) for real-time monitoring; subsequent separation of ethylene vinyl acetate (EVA) and glass layers using nanosecond and pulsed optical fiber lasers; and chemical etching with NaOH, HNO₃, and H₃PO₄ to recover high-purity metals. Findings: The study indicates that this integrated approach can achieve a silicon yield of 99.9984% and generate a total recycling profit of approximately 185.43 USD per kilogram of solar cells. The results demonstrate that automating the separation process significantly reduces manual labor and environmental risks while maximizing material recovery value. Conclusion: TeraCale constitutes a critical advancement in circular economy practices for the solar industry, effectively supporting Sustainable Development Goals 7 and 12. Novelty/Originality of this article: The novelty of this work is demonstrated by the unique combination of selective laser debonding and IoT-driven automation, providing a high-precision alternative to conventional destructive recycling techniques.